Development of MnZn ferrite as a transformer core material for switsh-mode power supplies (SMPS) - Maspol, Masdhiah (2001)
In electronics, magnetic transformer using ferrite cores are widely applied. In the recent years the rapid growth in popularity of Switched Mode Power Supplies (SMPS) units has led to a corresponding demand for high frequency ferrite cored power transformer. The main motivation for using ferrite transformer cores is the dramatic reduction of eddy current losses when compared with traditional iron core transformer. This study has been carried out to improve processing and understand the loss mechanisms of manganese zinc (MnZn) ferrite to meet the SMPS requirements. The preparation of the samples was typical for MnZn ferrite production utilizing wet method technique. The experimental work was divided into three parts namely the effect of composition, the effect of atmosphere control and the effect of additives. The effect of composition showed that MnZn ferrite sample with chemical composition of (MnO)0.335(ZnO)0.130 (Fe203)0.535 yield high initial permeability. µi values. The effect of controlling of the sintering atmosphere with the same composition did not achieve the desired result.µi dropped and Relative Loss Factor decreased. The effect of additives showed that 1n203 addition suppresed grain growth and V 20S cause duplex structure. which is the main reason, the µi declined. This can be concluded that to improve the magnetic characteristics is by controlling the microstructure by having an appropriate and proper controlling sintering scheme.